Influence of graphite morphology on the corrosion-fatigue properties of the ferritic Si-Mo-Al cast iron SiMo1000. (November 2020) - Xiang, Shengmei; Hedström, Peter; Zhu, Baohua; Linder, Jan; Odqvist, Joakim
Highlights: The fatigue life of SiMo1000 is more sensitive to graphite morphology than the testing atmospheres. Decreased nodularity causes reduced fatigue life and reduced decarburization resistance. The synergy of corrosion and fatigue affects the fatigue life of SiMo1000 only when nodularity is low. Abstract: The influence of graphite morphology on the corrosion-fatigue mechanism in the cast compacted graphite iron SiMo1000 is investigated. Two batches of SiMo1000 with the same chemical composition but different nodularity are tested using low-cycle-fatigue tests in argon and a synthetic exhaust atmosphere at 800 °C. Decreased graphite nodularity is found to significantly reduce the corrosion resistance of SiMo1000, causing severe decarburization on the sample surface. Besides, the fatigue life is also dramatically reduced with decreased graphite nodularity. The synergy of decarburization and fatigue is found to reduce fatigue life in one of the batches.